Halal Healthcare Investment: Evaluating CR, DER, and ROE Impacts on Sharia-Compliant Stock Prices (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
This study aims to analyze the effect of the Current Ratio (CR), Debt-to-Equity Ratio (DER), and Return on Equity (ROE) on the stock prices of healthcare companies classified as sharia-compliant on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. The background of the study is motivated by notable stock price fluctuations among sharia healthcare issuers, such as the sharp decline in PT Kimia Farma Tbk and price dynamics of other issuers including KLBF, MIKA, PEHA, and SIDO. The analysis uses a quantitative approach applying Partial Least Squares – Structural Equation Modeling (PLS-SEM) implemented in WarpPLS 8.0. The results indicate that CR does not have a significant effect on stock price (p = 0.174), while DER has a negative but not statistically significant effect (p = 0.484). In contrast, ROE has a positive and significant effect on stock price (p < 0.001), making ROE the dominant factor influencing investor interest. Simultaneously, the three independent variables explain only 20.2% of stock price variation, while the remaining 79.8% is influenced by factors outside the research model. The Tenenhaus goodness of fit (GOF) value of 0.450 suggests the research model has good overall quality despite the limited explanatory power of the tested financial variables.